Analisis tipe gaya kepemimpinan yang berpengaruh terhadap kinerja karyawan PT Ayo Media Network - Winata Handojo; Amani Ahmed Sulaiman Al Juhani; Desi Indah Nur Apiani; Johan Johan (Universitas Kristen Maranatha, 2021)
Ayo Media Network is one of the media companies that has successfully adapted to the development of technology and communication and has an excellent performance in providing news and other content. The performance is influenced by various factors, where one of the most important is the leadership style shown by the leader which consists of the leadership style of instructive, consultative, participation, and delegation. The purpose of this study was to find out the influence of each leadership style on employee performance at Ayo Media Network. Ayo Media Network has 91 workers who are the object and research respondents. The research methods used in this research were descriptive and explanatory. The results obtained that there is no influence between the leadership style of instructive and consultative on employee performance, while the leadership style of participation and delegation has a positive influence on employee performance.